Analisis Nikah Misyar Perspektif Yusuf Al Qaradhawi: Kajian Maslahah al-Mursalah - Ishak, Andi Muh. (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This study aims to find out the law of Misyar marriage according to the view of Yusuf Al Qaradhawi and to find out the validity of Misyar's marriage from the perspective of Maslahah. This research uses qualitative methods. The data collection process is carried out with literature studies. In analyzing data, researchers use qualitative analysis techniques with steps of data exposure, data reduction, and drawing conclusions. The results of the author's research found that: (1) Misyar's marriage law according to Yusuf Al Qaradhawi is valid if it is carried out as befits an ordinary marriage, that is, it meets all its pillars and conditions, it is done consensually, there is a guardian, there are witnesses, and there is a dowry. (2) Misyar marriage is a marriage in which a wife is allowed to give up some of her rights as a wife and the husband gives up some of her obligations as the head of the household. Misyar marriage is viewed from the point of view of maslahah, namely the istislah bi al-'urf method, namely choosing the benefit that best suits the needs of the community, especially Indonesia, then Misyar marriage should be prohibited in Indonesia, on the basis of the consideration that its hypocrisy is far greater than the benefits, and although it is legal according to the syar'i view, but there is no legal power in the context of the Indonesian state and also injures the point of the purpose of marriage including creating sakinah family, mawaddah warahmah.